المنھاج الغذائي للأطفال المصابین بالسكري النوع الأول وعلاقتھ بالنمو الجسمي ( الوزن والطول ) (Journal of the College of Education for Women, 2019)
Type 1 Diabetes melittus ( T1DM ) is Considered as one of thecomplicated and chronic disease that affects the dietary patterns for diabeticchild and his normal growth . for this reason , this study aimed to find therelationship between nutrient needs , the type of feeding for the diabetic childand his physical growth ( weight and height ) .The study includes 50 diabetic children , (28) females and (22) males whocame to the National Diabetes Center – AL-mustansiriya University for makingterm tests during the period from April 2009 to January 2010 .Their agesranged from 3 to13 years ,personal information were collected by aquestionnaire , weight and height were recorded and blood sample weretaken for Glycosylated Hemoglobin (HbA1c)measurement .The results revealed a reduction in the average total calories intake by theage group of (4-8) years and (9-13) for both males and females respectively.Results also showed 44% weight loss in the sample of the study .Thepercentage loss of males is higher than the females ( 45.5% , 42%)respectively and reduction in the average height . As for the HbA1c test, thestudy finds increasing average (9.1%) for males and (9.5%) for females.Those children who suffer from weight loss have higher average of HbA1c .The study shows , there is a significant correlation between total caloricintake , age and the HbA1c.